Markers of Oxidative and Nitrosative Stress in Systemic Lupus Erythematosus: Correlation with Disease Activity - Wang, Gangduo (2010)
OBJECTIVE: Free radical-mediated reactions have been implicated as contributors in a number of autoimmune disease (ADs) including SLE. However, potential of oxidative/nitrosative stress in eliciting an autoimmune response, or in disease prognosis and pathogenesis in humans remains largely unexplored. This study investigates the status and contribution of oxidative/nitrosative stress in SLE. METHODS: Sera from 72 SLE patients with various SLE scores [SLE disease activity index (SLEDAI)] and 36 age- and gender-matched controls were evaluated for oxidative/nitrosative stress markers, such as anti-malondialdehyde (MDA)- and anti-4-hydroxynonenal (HNE)-protein adduct antibodies, MDA-/HNE-protein adducts, superoxide dismutase (SOD), nitrotyrosine and iNOS. RESULTS: Serum analysis showed significantly higher levels of both anti-MDA-/anti-HNE-protein adduct antibodies and MDA-/HNE-protein adducts in SLE patients. Interestingly, our data showed not only increased number of subjects positive for anti-MDA- or anti-HNE-protein antibodies, but also greater increases in both these antibodies in SLE patients with greater SLEDAI (≥ 6), which were significantly higher than the lower SLEDAI group (<6). Data also showed a significant correlation between anti-MDA or anti-HNE antibodies and SLEDAI (r = 0.734 and 0.647 for anti-MDA and anti-HNE antibodies, respectively) suggesting a possible causal relationship between these antibodies and SLE. Furthermore, sera from SLE patients had lower levels of SOD, and higher levels of iNOS and nitrotyrosine. CONCLUSION: Our findings support an association between oxidative/nitrosative stress and SLE. Stronger response in samples with higher SLEDAI suggests that oxidative/nitrosative stress markers may be useful in evaluating the progression of SLE as well as in elucidating the mechanisms of disease pathogenesis.